1999
DOI: 10.1207/s15327655jchn1603_4
|View full text |Cite
|
Sign up to set email alerts
|

Motivating the Well Elderly to Exercise

Abstract: Most older adults hope to remain independent until death, but their inactivity, poor nutrition, and disabling diseases contribute to the loss of functions that are necessary for independence. Although exercise has been shown to improve a person's functioning and decrease health care costs, two thirds of persons over age 65 do not exercise regularly. The purpose of this article is to describe intervention strategies and evaluate their usefulness in motivating adherence to an exercise program designed specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 9 publications
2
31
0
Order By: Relevance
“…Some of the elderly individuals had the perception that exercise was not suitable for them anymore and the daily activity that they were doing was enough to be considered exercise 23. A general misconception of modern culture is to accept that old age is a time for relaxation and that physical activity and exercise are unnecessary or even harmful 24.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the elderly individuals had the perception that exercise was not suitable for them anymore and the daily activity that they were doing was enough to be considered exercise 23. A general misconception of modern culture is to accept that old age is a time for relaxation and that physical activity and exercise are unnecessary or even harmful 24.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has provided evidence that leisure activity involvement is associated with a reduced risk of disease and chronic illnesses (Grove & Spier, 1999), improved physical strength and functions (Skelton, Young, Greig, & Malbut, 1995), and increased muscle strength and joint flexibility (Hellman, 1997; Plonczynski, 2000). In addition, researchers have found that through leisure activity, older adults reported that they experienced positive psychological and mental health aspects, such as happiness, enjoyment, and positive emotions and feelings (Buettner & Fitzsimmons, 2002; Heo & Lee, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies focus on adult involvement in exercise and suggest that adults participate in exercise for the following motivations: personal challenge, a sense of achievement, weight loss, physical fitness, enjoyment, affiliation, and overall health improvement (Kilpatrick et al, 2005;Mathes & Battista, 1985;Summers, Machin, & Sargent, 1983). Exercise plays an important role in helping older adults maintain functional performance (Grove & Spier, 1999;Resnick, 2000). The benefits of regular exercise for older adults include improved cardiopulmonary function, lower blood pressure, increased bone mineral content, increased muscle strength and joint flexibility, and a heightened level of energy (Hellman, 1997;Plonczynski, 2000).…”
Section: The Relationship Between Exercise Motivation and Exercise Pamentioning
confidence: 99%